KANDUNGAN NUTRISI DAN PROFIL MIKROBA TEPUNG LIMBAH PETERNAKAN BROILER TERFERMENTASI - A. A., OKA; ARIANA, I. N. T.; ARDANI, T. I. A. S (Majalah Ilmiah Peternakan, 2023)
The nutritional and safe content of pathogenic bacteria in animal feed is something that must be considered ca- refully when looking for alternative feed sources. Potency and laboratory tests to determine the nutritional content and microbial profile must be carried out before being given to livestock. The by-product of the broiler farming bu- siness is broiler farming waste or “LPB”, which has the potential to be a source of animal feed concentrate. The aim of this research is to determine the nutritional content and microbial profile of broiler farm waste so that it can and is safely used as a source of animal feed. The research used field observation methods, proximate testing (to deter- mine the nutritional content of ingredients), followed by comparative methods (comparing the results of proximate testing of ingredients with the nutritional content of commercial concentrates). Research results, proximate anal- ysis of the nutritional content of LPB flour: crude protein: 36.98%, gross energy: 4,422 Kcal/gram. LPB microbial profile was declared negative for Eschericia coli and Salmonella shigella, Coliform < 3.0 CFU/g, mold 200 CFU/g. It can be suggested that the nutritional content and microbial profile of broiler farm waste flour can and is safely used as an alternative feed source.